Propuesta de capacitación y difusión de plantas nativas para uso en jardines sustentables - Bugallo, Veronica Lucia; Deane, Cecilia; Agüero, Juan I.; Fernandez, Martín Nicolás; Riccardo, María Laura; Facciuto, Gabriela Rosa (Sociedad Argentina de Botánica, 2026)
Poster